When the Perpetrator Is a Partner: Arrest and Charging Decisions in Intimate Partner Sexual Assault Cases—A Focal Concerns Analysis. (May 2017) - O'Neal, Eryn Nicole; Spohn, Cassia
Law enforcement officials and prosecutors have been called "gatekeepers" of the criminal justice system, as their discretionary decisions determine case outcomes. Using the focal concerns perspective as our theoretical foundation, we explore the factors that influence arrest and charging decisions in intimate partner sexual assaults (IPSA) reported to Los Angeles law enforcement in 2008. Quantitative findings are supplemented with qualitative examples from Los Angeles Police Department (LAPD) detectives interviewed in 2010 and charge evaluation sheets from complaints referred to Los Angeles prosecution in 2008. Attempting to expand its theoretical relevance, we develop an alternative conceptualization and operationalization of the focal concerns perspective that is more appropriate to IPSA cases. Findings suggest that arrest decisions are motivated by suspect blameworthiness, community protection, and practical constraints and organizational consequences. In addition, charging decisions are influenced by community protection and practical constraints. Extralegal factors did not influence decision making. Directions for future research are discussed.